Tumour stem cells in meningioma: A review. (January 2018) - Shivapathasundram, Ganeshwaran; Wickremesekera, Agadha C.; Tan, Swee T.; Itinteang, Tinte
Highlights: There is increasing evidence of the presence of tumour stem cells within meningioma. Stem cell markers are used to characterise this putative primitive population. They include OCT4, SOX2, NANOG, c-Myc, KLF4, CD133, nestin and vimentin. Abstract: Meningioma is a common intracranial and intraspinal neoplasm accounting for 25–30% of all primary neurological tumours. It is associated with high rates of recurrence especially in higher-grade tumours and lesions located at the skull base. Cancer stem cells are increasingly recognised as the origin of cancer and are attributed to loco-regional recurrence, metastasis and treatment resistance. This review presents the accumulating evidence of the presence of tumour stem cells within meningioma and the stem cell markers being used to characterise this putative primitive population within this common tumour.